SUPERFÍCIES E (DES)CONSTRUÇÕES NO PROCESSO VIDEOGRÁFICO NA DÉCADA DE 1980, EM VITÓRIA/ES - Guimaraes, Ernandes Zanon (2020)
The emergence of video in the 1960s in the USA, placed new technologies at the center of the contemporary art debate, causing transformations that redefined the processes of audiovisual production and circulation. The video developed as a hybrid language,